Effect of antituberculosis treatment on CYP2C19 enzyme activity in genetically polymorphic South Indian Tamilian population. (26th July 2016) - Xavier, Alphienes Stanley; Kumar, Saka Vinod; Sundaram, Rajan; Francis, Jose; Shewade, Deepak Gopal
Abstract: Patients on antituberculosis therapy (ATT) are more prone to drug interactions in the presence of coexisting illnesses which require drug therapy. Rifampicin is a pleiotropic inducer of CYP enzymes, and isoniazid is an enzyme inhibitor. Genetic variations are common in the gene coding for CYP2C19 enzyme. These variations would be important in predicting the individual variations in CYP2C19 activity. The objectives of the study were to find the net effect of 1‐month ATT on CYP2C19 enzyme activity and its association with CYP2C19 genetic polymorphisms. Newly diagnosed tuberculosis patients ( n = 125) were included in the study. Before commencing ATT, they were given a single dose of omeprazole 20 mg as a probe drug for CYP2C19. Blood sample was collected after 3 h to carry out phenotyping for CYP2C19 enzyme by measuring omeprazole hydroxylation index (OHI) using LC‐MS/MS. The phenotyping procedure was repeated after 1 month of ATT. CYP2C19 genotyping was carried out by PCR‐RFLP method. Significant reduction in OHI was observed after 1 month of ATT in all the metabolizer groups. The percentage reduction in OHI was maximum with poor metabolizers, 84.1 (IQR – 74.6, 86.6), and minimum with ultra‐rapid metabolizers, 39.6 (IQR – 12.7, 54.7). CYP2C19 enzyme induction is predominant in patients after 1 month of antituberculosis treatment (ATT). Genetic variations in the enzyme could not clearly explain the interindividual differences in induction. There is a potential risk of drug failure/adverse effect in poor metabolizers regardless of their genotype after ATT.